Image and translated Al-Quran verses retrieval system using thesaurus approach based on Malay query words / Mohd Zaini Mat Abas - Mat Abas, Mohd Zaini (2001)
Information can be in the form of texts, images or sounds. Current technology features allow Internet users to retrieve any documents that available in the online database from remote hosts or locally. The main issue in this information age was the efficiency and effectiveness of the retrieval system that used by the information provider. A good retrieval system should provide tools to perform searching accurately based on user requirement. The study of information retrieval is how to determine and retrieve from a mass of prepared information; the part that is relevant to particular information needs. There are many methods available to achieve this objective. Conflation is one of it. In English and French language conflation methods have been successful to identify words variants from present and historical database. As well as Malay language, conflation methods such as string-similarity method and stemming algorithms have been applied to Malay documents retrieval system. Another way of conflating related term is a thesaurus, which lists synonymous terms, and sometimes the relationship between them. In thesaurus approach, the behaviors of the language and the subject areas are important because it was totally language dependent. This study has evaluated and identified the effectiveness of thesaurus in Malay document retrieval system using Al-Quran test collections which consists AlQuran documents, Al-Quran images, relevant judgments and one set of queries. As the result of this study, a retrieval system that used thesaurus will be obtained more retrieved documents compare to exact match searching. However, it will reduce the efficiency and the effectiveness of the retrieval system. Although, it can be better if a proper study on this area can be perform together with a specialist who have good Islamic knowledge.